A novel hematopoietic progenitor cell mobilization regimen, utilizing bortezomib and filgrastim, for patients undergoing autologous transplant. Issue 6 (4th March 2016) - Abhyankar, Sunil; Lubanski, Philip; DeJarnette, Shaun; Merkel, Dean; Bunch, Jennifer; Daniels, Kelly; Aljitawi, Omar; Lin, Tara; Ganguly, Sid; McGuirk, Joseph
Abstract : Adequate hematopoietic progenitor cell (HPC) collection is critical for patients undergoing autologous HPC transplant (AHPCT). Historically, 15 − 30% of patients failed HPC mobilization with granulocyte‐colony stimulating factor (G‐CSF) alone. Bortezomib, a proteasome inhibitor, has been shown to down regulate very late antigen‐4 (VLA‐4), an adhesion molecule expressed on HPCs. In this pilot study, bortezomib was administered on days −11 and −8 at a dose of 1.3 mg/m 2 intravenously (IV) or subcutaneously (SQ), followed by G‐CSF 10 mcg/kg SQ, on days −4 to −1 prior to HPC collection (Day 1). Nineteen patients, with multiple myeloma ( n = 12) or non‐Hodgkin lymphoma ( n = 7) undergoing AHPCT for the first time, were enrolled. Patients were excluded if they had worse than grade II neuropathy or platelet count less than 100 x 10 9 /L. Bortezomib was well tolerated and all patients had adequate HPC collections with no mobilization failures. One patient (6%) had a CD34 + cell count of 3.9 cells/µL on Day 1 and received plerixafor per institutional algorithm. Eleven patients completed HPC collection in 1 day and eight in 2 days. All patients underwent AHPCT and had timely neutrophil and platelet engraftment. Comparison with a historical control group of 70 MM and lymphoma patients, who were mobilized with G‐CSF, showed significantly higher CD 34+ cells/kg collected in the bortezomib mobilization study group. Bortezomib plus G‐CSF is an effective HPC mobilizing regimen worth investigating further in subsequent studies. J. Clin. Apheresis 31:559–563, 2016. © 2015 Wiley Periodicals, Inc.